Reconnection
XII, 218 p.
Keywords: This book is based on the work of a European partnership, whose members came together from Belgium England Finland Germany Portugal and Greece with the support of funding from the EU Socrates Programme. Our goal was to work collaboratively to generate new ways of thinking about the situation of people aged between 14 and 25 who are at risk of (or experiencing) social exclusion, set in the context of a unique international analysis of policies, contexts and perspectives on the problems of social exclusion in Europe and the challenges of promoting lifelong learning among those who have rejected it early in life. We set out to examine programmes which help people to RE-ENTER pathways of education and training, but ended with approaches which are better characterised by their ability to RECONNECT people, not only to opportunities in the social structures but also to each other and to their communities We have developed new models and guidelines based on analysis of the best of European practice using the distinctive approaches of 'situated learning'. By an iterative and collaborative method of working, we have arrived at the concept and approaches of Learning Communities Centred on Practice (LCPs), which lie at the heart of this volume.